2015
DOI: 10.1016/j.jtcvs.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic structural heart changes in early tricuspid regurgitation

Abstract: Tricuspid annular dilation and right/left atrial enlargement comprise early events in mild functional tricuspid regurgitation. Atrial enlargement occurs before right ventricular dilation, which occurs late, when tricuspid regurgitation is severe. Atrial volume and tricuspid annular dilation are early and sensitive indicators of tricuspid regurgitation significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 45 publications
(45 reference statements)
2
31
0
Order By: Relevance
“…The grade of TR shows the advanced state of cardiac disease most often reflecting left sided valvular disease 18–20. In patients with left sided valvular disease, the elevated left atrial pressure is reflected through an elevated pulmonary artery pressure which in turn causes RV dilation and worsening of secondary TR 10 21. However, it does not follow a similar course in reverse.…”
Section: Discussionmentioning
confidence: 99%
“…The grade of TR shows the advanced state of cardiac disease most often reflecting left sided valvular disease 18–20. In patients with left sided valvular disease, the elevated left atrial pressure is reflected through an elevated pulmonary artery pressure which in turn causes RV dilation and worsening of secondary TR 10 21. However, it does not follow a similar course in reverse.…”
Section: Discussionmentioning
confidence: 99%
“…Thin image slices allow for detection of distinct valvular boundaries and useful spatial information for assessing RV function [67]. Studies support the prognostic value of cardiac CT for indexing FTR—such parameters include the RA and RV volumes, the leaflet tethering angles and height, and the annular diameter and area [68,69,70]. CT has also been used in the post-operative assessment of annuloplasty ring dislodgment and quantification of the spatial relationship between pacemaker leading in the RV and the associated TR [67,68,71].…”
Section: Functional Tricuspid Regurgitation: Diagnosis and Treatmementioning
confidence: 99%
“…Functional tricuspid regurgitation (TR) is the result of either tricuspid annular dilation or increased chordal tethering. Annular dilation is strongly correlated to both right atrial and right ventricular (RV) dilation 1 . Since Dreyfus et al 2 demonstrated that TR may further impair even after successful mitral valve (MV) surgery, most surgeons started to treat less than severe TR in the presence of a dilated annulus (>40 mm or >21 mm/m 2 ) 3,4 .…”
Section: Introductionmentioning
confidence: 99%